2008
DOI: 10.1086/528946
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Solar‐like Oscillations in the G5 Subgiant μ Her

Abstract: A clear detection of excess of power, providing a substantial evidence for solar-like oscillations in the G5 subgiant µ Her, is presented. This star was observed over seven nights with the SARG echelle spectrograph operating with the 3.6-m Italian TNG Telescope, using an iodine absorption cell as a velocity reference. A clear excess of power centered at 1.2 mHz, with peak amplitudes of about 0.9 m s −1 in the amplitude spectrum is present. Fitting the asymptotic relation to the power spectrum, a mode identific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 12 publications
0
42
2
Order By: Relevance
“…2), but observable from the northern hemisphere, can be found in the PASTEL catalogue. These are HD 73752 (HR 3430, [Fe/H] = 0.4, Luck & Heiter 2006), a close visual binary (5.4 and 6.8 mag, period of 123 yr, semi-major axis of 1.7 arcsec, Malkov et al 2012);HD 19994 (GJ 128) and HD 120136 (τ Boo, GJ 527), two planet-host visual binaries (semi-major axes 10 and 5 arcsec, Malkov et al 2012;Poveda et al 1994) Silva et al 2011), a star with asteroseismic data (Bonanno et al 2008), for which Baines et al (2014) measured an angular diameter of 1.96 ± 0.01 mas with the NPOI.…”
Section: Appendix A: Hr-diagrams For Individual Starsmentioning
confidence: 99%
“…2), but observable from the northern hemisphere, can be found in the PASTEL catalogue. These are HD 73752 (HR 3430, [Fe/H] = 0.4, Luck & Heiter 2006), a close visual binary (5.4 and 6.8 mag, period of 123 yr, semi-major axis of 1.7 arcsec, Malkov et al 2012);HD 19994 (GJ 128) and HD 120136 (τ Boo, GJ 527), two planet-host visual binaries (semi-major axes 10 and 5 arcsec, Malkov et al 2012;Poveda et al 1994) Silva et al 2011), a star with asteroseismic data (Bonanno et al 2008), for which Baines et al (2014) measured an angular diameter of 1.96 ± 0.01 mas with the NPOI.…”
Section: Appendix A: Hr-diagrams For Individual Starsmentioning
confidence: 99%
“…Timeseries were prepared for asteroseismic analysis in the manner described by García et al (2011). Different teams attempted to detect, and then extract the basic properties of, the solar-like oscillations using automated analysis pipelines developed and extensively tested (e.g., see Bonanno et al 2008;Huber et al 2009;Mosser & Appourchaux 2009;Roxburgh 2009;Campante et al 2010;Hekker et al 2010;Mathur et al 2010) for application to the large ensemble of targets observed by Kepler. The basic results of this survey were presented in Chaplin et al (2011) and Verner et al (2011).…”
Section: δν δνmentioning
confidence: 99%
“…ORK applied a procedure known as iterative sine-wave fitting (ISWF; e.g., Bedding et al 2007;Bonanno et al 2008;White et al 2010): it iteratively removes sinusoidal components from the data, which are identified as the maxima of the Fourier spectrum of the residuals. Since the number of oscillation modes present in the data is unknown a priori, the algorithm requires a stopping rule that associates some degree of confidence to the amplitude of each extracted sinusoidal component.…”
Section: Overview Of the Different Fitting Strategiesmentioning
confidence: 99%